2017
DOI: 10.1080/21663831.2017.1343207
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced substitutional reaction of Fe into Mo2GaC thin films

Abstract: The first Fe-based MAX phase is realized by solid-state substitution reaction of an Fe/Au/Mo 2 GaC thin-film diffusion couple, as determined by X-ray diffraction and scanning transmission electron microscopy. Chemical analysis together with elemental mapping reveals that as much as 50 at.% Fe on the A site can be obtained by thermally induced Au and Fe substitution for Ga atomic layers in Mo 2 GaC. One-sixth of the original Ga is also replaced by Au atoms. When annealing Mo 2 GaC thin films covered with Fe onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…As can be observed in both images, one darker layer (the A elements) interleaves two adjoining brighter layers of Nb with larger atomic mass. The presented images are similar to STEM images of other M2AX phases having the characteristic zig-zag stacking of the 211 Mn+1Xn layers[6,12]. InFigure 4(c), the atomic-resolved EDS element mapping and line-scan of Nb-Lα and Cu-Kα further identified the atom position of Cu, all at A sites, corroborating the synthesis of Nb2CuC MAX phase through a replacement reaction, to form a MAX phase with only Cu on the A site.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…As can be observed in both images, one darker layer (the A elements) interleaves two adjoining brighter layers of Nb with larger atomic mass. The presented images are similar to STEM images of other M2AX phases having the characteristic zig-zag stacking of the 211 Mn+1Xn layers[6,12]. InFigure 4(c), the atomic-resolved EDS element mapping and line-scan of Nb-Lα and Cu-Kα further identified the atom position of Cu, all at A sites, corroborating the synthesis of Nb2CuC MAX phase through a replacement reaction, to form a MAX phase with only Cu on the A site.…”
supporting
confidence: 73%
“…By now, more than 80 members of ternary MAX compositions have been discovered [5]. Recent studies have also demonstrated that the A-site element in MAX phases can be a late transition metal (e.g., Au, Ir, Zn, Fe and Cu) [6][7][8][9][10][11][12][13]. Transition metals have distinct properties different from other A-group elements due to their large d electron orbits.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in order to overcome the interference of competing phases on the formation of targeting MAX phases, an isomorphous replacement approach was developed. This replacement strategy takes advantage of chemically stable Mn+1Xn slabs, with a full replacement reaction of the A atoms between these slabs in nanolaminated MAX phases by annealing in contact with a metal reservoir [7][8][9][10] , or a Lewis acid molten salt [11][12][13] to achieve atomic-layer-exchange in a confined single-atom-thick 2D space. Since H. Notwotny et al reported the first MAX phase in the 1960's [14][15] , this isomorphous replacement strategy has resulted in groundbreaking new ternary MAX phases (such as Ti3AuC2 [7] , Ti3IrC2 [7] , Mo2AuC [9] , Ti3ZnC2 [11] , Ti2ZnC [11] , V2ZnC [11] , Ti2ZnN [11] and Nb2CuC [13] ).…”
Section: Introductionmentioning
confidence: 99%
“…30,31 A substitutional reaction involving an Fe + Au alloy has also been used to introduce Fe into the MAX phase A-layer. 18 Here, we report on synthesis and characterization of a novel magnetic MAX phase, (Cr 0.5 Mn 0.5 ) 2 AuC obtained from the substitutional solid state reaction between a (Cr 0.5 Mn 0.5 ) 2 GaC thin film and an Au-capping layer. The discovery of the (Cr 0.5 Mn 0.5 ) 2 AuC phase is not only a new material, but more importantly it provides a direct method for modifying the magnetic properties of inherently nanolaminated carbides with different A elements.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…15 Experimental studies have also been done on attaining magnetic MAX phases by alloying Fe on the M sites 16,17 or the A sites. 18 For a more comprehensive summary, please see the review in Ref. 19.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%